Deficient pregnenolone synthesis associated with congenital adrenal hyperplasia and organelle dysfunction. (3rd May 2019) - Bose, Himangshu S; Rice, Alan M; Marshall, Brendan; Gebrail, Fadi; Kupshik, David; Perry, Elizabeth W
Summary: Steroid hormones are essential for the survival of all mammals. In adrenal glands and gonads, cytochrome P450 side chain cleavage enzyme (SCC or CYP11A1), catalyzes conversion of cholesterol to pregnenolone. We studied a patient with ambiguous genitalia by the absence of Müllerian ducts and the presence of an incompletely formed vagina, who had extremely high adrenocorticotropic hormone (ACTH) and reduced pregnenolone levels with enlarged adrenal glands. The testes revealed seminiferous tubules, stroma, rete testis with interstitial fibrosis and reduced number of germ cells. Electron microscopy showed that the patient's testicular mitochondrial size was small with little SCC expression within the mitochondria. The mitochondria were not close to the mitochondria-associated ER membrane (MAM), and cells were filled with the microfilaments. Our result revealed that absence of pregnenolone is associated with organelle stress, leading to altered protein organization that likely created steric hindrance in testicular cells. Learning points: Testes revealed seminiferous tubules, stroma, rete testis with interstitial fibrosis and reduced number of germ cells; Testicular mitochondrial size was small with little SCC expression within the mitochondria; Absence of pregnenolone is associated with organelle stress.